PROJECTS OF EUROPEAN COUNTRIES TERRITORIES RECONNAISSANCE SURVEY BY DIRECT-PROSPECTING METHODS IN ORDER TO IDENTIFY PROMISING AREAS FOR OIL AND GAS DETAILED EXPLORATION - Mykola Yakymchuk; Ignat Korchagin (World Scientific Reports, 2023)
The article presents a brief description of projects for the territories of European countries surveying in the reconnaissance mode in order to identify promising areas and sites for detailed prospecting for oil and gas, natural hydrogen. Prepared projects of reconnaissance survey of individual countries can be quickly implemented with using the mobile and low-cost technology, that include modified methods of frequency-resonance processing and decoding of satellite and photo images, vertical electric-resonance sounding of a cross-section, as well as a method of integrated assessment of the prospects of oil and gas potential of large prospecting blocks and license areas. For these projects practical implementation, the satellite image of the European countries territories are divided into separate blocks (fragments), the frequency-resonance processing of which may be carried out separately. During image fragments processing, the following set of measurement procedures may be performed: a) fixation of responses at the frequencies of oil, condensate and gas; b) registration of signals at the frequencies of methane-oxidizing bacteria; c) establishing the presence of a volcanic structures in which there are conditions for the hydrocarbon’s synthesis at a depth of 57 km; additional fixation of responses of oil, condensate and gas at this depth; d) fixing signals at the frequencies of oil, condensate and gas from the lower part of cross-section at depths of 5 km, 10 km, 15 km in order to assess the prospects of oil and gas discovering in the deep horizons of cross-section. The listed procedures of instrumental measurements have fully demonstrated their effectiveness and informativeness in the process of direct-prospecting methods approbation in the areas (sites) of exploratory wells drilling on land and shelf in various regions of the globe. The developed super-mobile direct-prospecting technology has provided the authors with a unique opportunity to conduct a huge number of experiments in various regions of the globe. In the process of experimental work conducting, numerous evidence was obtained in favor of the deep (abiogenic) genesis of hydrocarbons in the framework of the concept of hydrogen degassing of the Earth. The proven technology allows filling the studied cross-section with specific rocks (sedimentary, metamorphic and magmatic), as well as identifying areas on the surface and intervals in the cross-section that are promising for ore and combustible minerals prospecting. The super-mobile methods can be used to assess the prospects for oil and gas (ore) potential of large exploration blocks and local areas (including those put up for auction), to select the optimal locations (sites) for laying exploration and production wells, assessment of the prospects for discovering oil and gas deposits in the deep and super-deep horizons of cross-section, prospecting and localization of zones with deep channels location, through which the chemical elements, fluids and mineral matter migrate into the upper horizons of cross-section. The use of mobile and low-cost technology will significantly speed up the exploration process for oil, condensate, gas, natural hydrogen, as well as reduce the financial costs for its implementation